Analisis Perbandingan Biaya Penggunaan Perancah Kayu Galam Dan Perancah Besi (Scaffolding) - Rafik, Aunur; Cahyani, Rinova Firman (Jurnal Teknik Sipil, 2018)
A scaffolding is a construction helper on building construction work. The scaffolding is made when the building work occupies a height of more than 2 meters and can not be reached by the workers. Because of the availability of galam wood in Banjarmasinis increasingly rare, thus the search for alternative material for scaffolding that is more durable, easier to get and can be used repeatedly is necessary to conduct. One of them is iron scaffolding. This research calculated and compared the cost of using galam wood scaffolding and iron scaffolding in the purchase price and rental price to find out which type of scaffolding is more economical to use. The method used in this research was descriptive method and comparative method . The locations of data retrieval were on the construction of Central Bureau of Statistics Office (BPS) South Kalimantan Province on Jl Trikora Banjarbaru and 3-storey building on Jl. Banua Anyar Banjarmasin. Based on the calculation in the area of 1m2 the cost of galam wood scaffolding work of Rp. 147,057,81, -, the iron scaffolding work in rental price of Rp. 201,033,81 and the cost of iron scaffolding in the purchase price of Rp. 2,214,161,06 obtained. These results showed that the cost of galam wood scaffolding work 26.85% cheaper than the iron scaffolding in the rental price and 15 times the cost of iron scaffolding in the purchase price. Keywords— Galam Wood Scaffolding, Iron Scaffolding, Budget Planning (RAB), Rental Price, Purchase Price